Tindak Pidana Korupsi Melalui Pencucian Uang dengan Memanipulasi Laporan Keuangan - Thesalonika Djumaifin; Felix Chandra P; Tries Ellia Sandari (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Corruption in Indonesia has evolved into a complex phenomenon, often involving money laundering and financial statement manipulation as mechanisms to conceal illicit assets within seemingly legal financial systems. This study focuses on the bribery case involving the Regent of Kepulauan Meranti as the research object, aiming to trace the flow of funds, financial manipulation techniques, and the involvement of both individual and corporate actors. The objective of this research is to analyze the interconnection between corruption, money laundering, and financial statement fraud, and to examine the legal implications of the criminal charges applied within Indonesia’s penal system. This study adopts a qualitative approach using a case study method, with primary data drawn from official documents issued by the Corruption Eradication Commission (KPK) and secondary data from credible media sources. The findings reveal that the corruption scheme was systematically carried out by disguising illegal funds through property investments and business entities. The study also highlights the insufficient application of cumulative charges and emphasizes the need for regulatory enhancement, particularly concerning illicit enrichment provisions. This research underscores the urgency of reforming supervision systems, penal structures, and strengthening the role of forensic accounting in detecting and preventing organized financial crimes in the public sector.